Building a New Breath: Empowering Local Cattle Breeders Through CV Enhal Farm, Dusun Simbolo, Tompobulu Village, Tompobulu District, Maros Regency - Octafani Rempe; Wahyuni Ramadani; Yulianti Eni; Mannuntungi; Azrizal Ridwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community empowerment is a series of actions that are systematic and involve various components of formal and non-formal organizations. The program is being carried out in the Kuncio hamlet, Tompobulu District, Maros Regency, South Sulawesi in an effort to improve the welfare of local Balinese cattle breeders as a form of true empowerment that has been carried out so far, such as coaching and training in caring for Balinese cattle through CV Enhal Farm. The purpose of this study was to find out an overview of the implementation of thewichom community empowerment program in the field of local bali cattle parenting social economy. This study uses qualitative research methods using descriptive research types, to describe research and research results. Data collection techniques in this study using observation techniques, interviews and documentation. The results showed that the implementation of the empowerment program for local Balinese cattle breeders changed people's lives in the economic, knowledge and spiritual fields.